Barriers to widespread adoption of telehealth from physicians' perspective: A survey in southern Iran. - Mohammad Hosein Hayavi-Haghighi; Niloofar Choobin; Jahanpour Alipour (PLoS ONE, 2025)
Introduction The widespread use of telehealth in healthcare institutions depends on removing its barriers. This study examines the barriers to the widespread adoption of telehealth in the teaching hospitals of Hormozgan University of Medical Sciences (HUMS). Methods A cross-sectional descriptive-analytical study was conducted in 2024 in three teaching hospitals. The study population included 239 physicians working at teaching hospitals of HUMS, all of them were included in the sample. Data collection was performed utilizing a questionnaire developed by the researchers. The analysis of the data involved both descriptive (mean and standard deviation) and analytical (Pearson's and Spearman's correlation coefficients) statistics. Results A total of 169 physicians completed and returned the questionnaire. The mean score of personal, technical, behavioral, organizational, legal, clinical, and financial from the physician's perspective was 3.83 ± 0.66, 3.81 ± 0.56, 3.75 ± 0.52, 3.66 ± 0.53, 3.64 ± 0.59, 3.59 ± 0.55, and 3.54 ± 0.67, respectively. The organizational factor had the highest correlation with others. Pearson's correlation test showed that there was a significant positive and fair correlation between the organizational factor and financial (r = 0.524, P < 0.01), clinical (r = 0.399, P < 0.01), technical (r = 0.308, P < 0.01), behavioral (r = 0.321, P < 0.01), and personal (r = 0.307, P < 0.01) factors. Conclusions The correlation between factors demonstrates that the success of telehealth necessitates the consideration of a multitude of interdependent dimensions. Training physicians, improving the delivery of healthcare to patients, and developing and updating guidelines for telehealth services are potential solutions for eliminating the barriers.